TEORI HUKUM BERBASIS KEWAJIBAN MENURUT IMMAUEL KANT - Petrus CKL Bello (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2024)
Law that is philosophically discussed by Immanuel Kant is related to morality, especially to individual autonomy. While law emphasizes the necessity of action according to external norms, morality actually orders humans to act according to their inner convictions. In this regard, Kant distinguishes between legality and morality. Legality is the mere conformity of an action to external law or norms, without considering the inner elements, while morality is the conformity of an action to the inner norm, namely the awareness of responsibility and obligation in a concrete situation. According to Kant, law is an instrument to promote moral values. If morality is essentially determined by the individual's capacity to determine themselves through their personal actions, then the effectiveness of law occurs on the contrary thanks to the power of institutions or authoritative bodies. However, the validity of the objectivity of both can only be accepted if both morality and law are open to intersubjective discourse. In Kant's philosophy, the understanding that uses this discursive imperative is publicity or publicity. Publicity is an essential element in the process of making law. In his book The Metaphysical Basis of Morality (Grundlegung zur Metaphysik der Sitten, 1785 abbreviated: GMS) Kant stated that an action is only moral if it is done for the sake of duty alone, not for other considerations. And to form such a moral command Kant mentioned several conditions or principles, for example the principle known as the 'general principle of law': "always act based on the maxim that you can at the same time will as general law" and "all actions related to the rights of others, whose maxims are not in line with publicity, are wrong." Kant's intention with the general principle of law is to find out whether an action taken must be carried out and whether my maxim can be universalized (made a general law for everyone). If "yes", the action must be carried out. If "no" the action is not mandatory. That is why Kant's ethics and legal theory are categorized as duty ethics (deontology) and duty-based legal theory.